2015
DOI: 10.1681/asn.2013101137
|View full text |Cite
|
Sign up to set email alerts
|

Curtailing Endothelial TGF-β Signaling Is Sufficient to Reduce Endothelial-Mesenchymal Transition and Fibrosis in CKD

Abstract: Excessive TGF-b signaling in epithelial cells, pericytes, or fibroblasts has been implicated in CKD. This list has recently been joined by endothelial cells (ECs) undergoing mesenchymal transition. Although several studies focused on the effects of ablating epithelial or fibroblast TGF-b signaling on development of fibrosis, there is a lack of information on ablating TGF-b signaling in the endothelium because this ablation causes embryonic lethality. We generated endothelium-specific heterozygous TGF-b recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
110
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 46 publications
4
110
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Several recent studies suggested that restoring the renal microvasculature may provide novel therapeutic options for patients with CKD. [8][9][10][11][12] Thus far, however, quantitative imaging tools allowing for the noninvasive monitoring of morphologic and functional alterations of the renal microvasculature during disease progression have been lacking, and studies investigating vessel rarefaction in CKD have been largely restricted to invasive microscopic end-point analyses. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] We here employed in vivo and ex vivo mCT-based imaging techniques, alongside conventional immunohistochemical methodologies, to demonstrate that (1) contrast-enhanced in vivo mCT imaging is highly suitable for accurate and noninvasive monitoring of vessel functionality during progressive kidney diseases, via quantifying the renal rBV; (2) the renal rBV continuously decreases during early-to-late-stage renal disease progression; (3) vessel functionality is reduced immediately after renal injury prior to the onset of interstitial fibrosis, supporting the assumption that endothelial injury might be a major initiating cause of fibrosis development; and (4) in addition to peritubular capillaries, arterial vessels of virtually all calibers undergo substantial alterations during progressive renal disease with regard to vessel branching, size, and tortuosity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Several recent studies suggested that restoring the renal microvasculature may provide novel therapeutic options for patients with CKD. [8][9][10][11][12] Thus far, however, quantitative imaging tools allowing for the noninvasive monitoring of morphologic and functional alterations of the renal microvasculature during disease progression have been lacking, and studies investigating vessel rarefaction in CKD have been largely restricted to invasive microscopic end-point analyses. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] We here employed in vivo and ex vivo mCT-based imaging techniques, alongside conventional immunohistochemical methodologies, to demonstrate that (1) contrast-enhanced in vivo mCT imaging is highly suitable for accurate and noninvasive monitoring of vessel functionality during progressive kidney diseases, via quantifying the renal rBV; (2) the renal rBV continuously decreases during early-to-late-stage renal disease progression; (3) vessel functionality is reduced immediately after renal injury prior to the onset of interstitial fibrosis, supporting the assumption that endothelial injury might be a major initiating cause of fibrosis development; and (4) in addition to peritubular capillaries, arterial vessels of virtually all calibers undergo substantial alterations during progressive renal disease with regard to vessel branching, size, and tortuosity.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 The TGF-b pathway is an important promoter of renal fibrosis often involved in renal disease from different etiologies. 37 In addition, TGF-b can also lead to renal fibrosis by promoting endothelial-to-mesenchymal transition and blunting angiogenesis, 38 an effect that may have contributed to MV rarefaction and the subsequent improvement following treatment. Therefore, an improvement in MMP-2/TIMP-1 coupled with an augmented MV proliferation may explain the expansion of the renal MV architecture after ELP-VEGF therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, microvascular dysfunction, damage, and even loss are hallmarks of renal disease in humans, which correlate with the development of renal dysfunction and injury and may both initiate and promote interstitial fibrosis, tubular atrophy, and glomerulosclerosis. 2,3 Unlike nephrons, with numbers that are determined at birth and (still) cannot be regenerated or recreated de novo, the vessels in the kidney are subject to changes in their diameter, remodeling, and possibly, repair and regeneration. Development of new vessels in the kidney is not limited to the developmental phase of the organ and serves as compensatory mechanism in response to insults that could also be activated or stimulated by therapeutic interventions.…”
mentioning
confidence: 99%